Factors Affecting Consumer-Based Brand Equity from the Perspective of Turkish Consumers - Akyüz, İlker; Bayram, Bahadır Çağrı; Ersen, Nadir (Faculty of Forestry, University of Zagreb, 2019)
This paper contributes to the consumer-based brand equity literature by researching what brand equity means for Turkish consumers and by defining factors that, from their perspective, affect Consumer-Based Brand Equity (CBBE). According to our literature review, although some important cross-cultural studies about CBBE can be found, some aspects of this topic require further research. The target population of the study is households in the Western Black Sea Region. This region was chosen because it is a manageable size, geographically close to the researchers, and statistically representative of the Turkish people. Turkish panel furniture (PF) brands were chosen as the sample, and a stratified sampling method was used to determine the questionnaires sample size. Data were analysed in SPSS, incorporating statistical tests such as factor analysis, correlation analysis and chi-square tests. Factors that affected CBBE were marketing activities, perceived quality, brand awareness, brand association and price.